The impact of intradialytic elastic band exercise on physical and cognitive abilities in patients on maintenance hemodialysis: a randomized controlled trial - Xianxuan Feng; Jingwen Sun; Zihan Wang; Nina Zhang; Yumei Liu; Zhenhong Wang; Niansong Wang; Guihua Jian; Dongsheng Cheng; Xiaohua Sheng; Yanhong Ma (Renal Failure)
Exercise benefits patients on maintenance hemodialysis (MHD) by addressing complications and dysfunctions. Elastic band exercise is cost-effective, but its safety, efficacy, and feasibility during dialysis are not well-established. The aim of this study is to investigate the physical and mental effects of intradialytic elastic band exercise in patients on MHD. Sixty patients on MHD were randomly assigned to the exercise or control group (30 patients/group). The control group received routine hemodialysis care, whereas those in the exercise group performed intradialytic elastic band exercises for 0.5–2 h during hemodialysis three times a week for 12 weeks. Physical function (Short Physical Performance Battery [SPPB]), cognitive function (Montreal Cognitive Assessment [MoCA]), fatigue (14-item Fatigue Scale [FS-14]), sleep quality (Pittsburgh Sleep Quality Index [PSQI]), and anxiety and depression (Hamilton Anxiety Rating Scale [HAMA]/Hamilton Depression Rating Scale [HAMD]) were assessed. The exercise group showed significant improvements in SPPB (p = 0.008) and MoCA (p < 0.001) scores compared to pre-intervention and control groups. FS-14 scores decreased significantly (p = 0.005). PSQI (p < 0.001) and HAMA (p < 0.001) scores improved post-intervention but not versus control. HAMD scores reduced significantly (p < 0.001). Satisfaction and recommendation scores were 9.57 and 9.71. In conclusions, intradialytic elastic band exercise improved physical and cognitive function and alleviated fatigue, sleep issues, depression, and anxiety in patients on MHD. With high compliance, no significant adverse events, and high patient satisfaction, it is recommended as a routine intervention during dialysis.